(untitled) (Hoboken, N.J., 2007)
This very impressive two-volume work presents descriptions of food product manufacturing, legal issues, specific ingredients, and food flavors. The 54 chapters that are devoted to the manufacturing of specific food products feature bakery, beverages, rice, noodles, cheeses, confectionery, fats and oils, fruits and juices, and functional foods in v.1 and meat, milk, poultry, seafood, and vegetables in v.2. Each of these chapters discuss background information on growing and harvesting, storage, varieties, and other issues before turning to aspects of production, including physico- chemical characteristics, and processing. Apple production, as an example, is considered for juice and cider, slices, applesauce, frozen, and dried. Newer food technologies are also included--processed fresh-cut fruits, for example--as are issues related to food production such as sanitation, quality assurance, sensory quality, and genetic engineering. A separate chapter is included on the standard industrial classification for food manufacturing in the U.S. Chapters are also included on food establishment inspection in the U.S. and all FDA food-related regulations. Each chapter concludes with a lengthy bibliography. Written by over 200 specialists worldwide, this thorough, well-rounded reference will be of use to food manufacturers, academics, and government and industrial professionals, as well as undergraduate and graduate students.
Keywords: Food industry and trade,Food; Composition